2013
DOI: 10.1016/j.jadohealth.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Parental Acceptability of Contraceptive Methods Offered to Their Teen During a Confidential Health Care Visit

Abstract: Purpose To examine parental acceptability of contraceptive methods offered confidentially to their adolescent daughter. Methods A random sample of 261 parents/guardians with a daughter between 12–17 completed a telephone survey examining the relationship between parental acceptability of seven contraceptive methods with adolescents’ likelihood to have sex, parenting beliefs, parents’ sexual health as teens, sexually transmitted infection (STI) knowledge, and demographic factors. Results Acceptability was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
(7 reference statements)
1
13
0
Order By: Relevance
“…Adolescence is characterized as a period of transition for youths as they mature into adulthood; likewise, the role of parents shifts during this time, with increasing autonomy given to the adolescent (49). Parental monitoring, which includes parental solicitation and adolescent disclosure of information as well as parental control, is associated with reduced risk behavior (50) and increased protective behavior, especially when parents recognize the autonomy of adolescents (51). Parental recognition of the autonomy of adolescents is associated with adherence to medications for chronic disease (52).…”
Section: Therapeutic Partnershipmentioning
confidence: 99%
“…Adolescence is characterized as a period of transition for youths as they mature into adulthood; likewise, the role of parents shifts during this time, with increasing autonomy given to the adolescent (49). Parental monitoring, which includes parental solicitation and adolescent disclosure of information as well as parental control, is associated with reduced risk behavior (50) and increased protective behavior, especially when parents recognize the autonomy of adolescents (51). Parental recognition of the autonomy of adolescents is associated with adherence to medications for chronic disease (52).…”
Section: Therapeutic Partnershipmentioning
confidence: 99%
“…Interviewer administered structured questionnaire was used to collect the data. The questionnaire was adapted from different literatures and considering the local situation of the study subjects [5,12,13]. The designed questionnaire was translated first into the local language, Tigrigna and back translated to English to ensure its consistency.…”
Section: Data Collection and Quality Controlmentioning
confidence: 99%
“…Thus, acceptance determines effective use and continuity of the chosen contraceptive method [11]. Low acceptability of long acting reversible contraceptive could have its own effect on the high unmet need of contraception's [12,13]. Even though short acting contraceptive methods are mainstays of women's contraceptive choices, they have lower continuation rates and higher pregnancy rates than long acting reversible contraceptives [11].…”
Section: Introductionmentioning
confidence: 99%
“…Time constraints and concerns of parental reaction are often cited as barriers to IUD discussion with adolescents 32. Both are legitimate concerns, and a study of parental acceptability of contraceptive options found that only 18% of those parents surveyed viewed the IUD as an acceptable option for adolescents 89. It is possible that parents view short-acting methods as associated with single sexual episodes, whereas longer-acting methods suggest an ongoing sexual relationship.…”
Section: Specific Considerationsmentioning
confidence: 99%